International Congress on Applications of Lasers &Amp; Electro-Optics 1998
DOI: 10.2351/1.5059185
|View full text |Cite
|
Sign up to set email alerts
|

Neural network modeling of weld pool shape in pulsed-laser aluminum welds

Abstract: The submitled mpnurcript has been aclhored by a contractor d the U. S. G o w r~ under coruract NO. OE-AC05-660%?2464. Acootdingly. the U.S Government retains a nonexdwve., royaly-tree license lo puMish or reproduce !he pubiished form of this contribrtbn, of alow others to do so. for US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Thus, depending on the base alloy composition, the role of the alloying elements varies. Similar observations were reported by Vitek et al 12 The role of Ni, N, Mn, and Cu as austenite stabilisers is in agreement with reports by Kotecki. 3 The role of Si and Nb as an austenite stabiliser in alloy 255 is reported here for the first time.…”
Section: Composition Dependence Of Fn Value In Duplex Stainless Steelsupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, depending on the base alloy composition, the role of the alloying elements varies. Similar observations were reported by Vitek et al 12 The role of Ni, N, Mn, and Cu as austenite stabilisers is in agreement with reports by Kotecki. 3 The role of Si and Nb as an austenite stabiliser in alloy 255 is reported here for the first time.…”
Section: Composition Dependence Of Fn Value In Duplex Stainless Steelsupporting
confidence: 93%
“…The size and shape of the error bar in each figure depends on the distribution and noise of the training dataset used. It was found that C, Ni, and N act as austenite stabilisers, with N having a stronger effect than C. This is in agreement with the results reported by Vitek et al 12 Although the Mn content in the training dataset varied from 0?5 to 1?98 wt-% for duplex stainless steel welds, the variation in Mn content was found not to influence the FN. The observation that variation in Mn does not influence the FN is in agreement with that reported by Szumachowski and Kotecki 22 for austenitic stainless steel welds.…”
Section: Composition Dependence Of Fn Value In Duplex Stainless Steelsupporting
confidence: 91%
See 3 more Smart Citations